Scholarship Acceptance Decision Support System at SMKN 4 Bengkulu City using the AHP method - Melinda Apriyani; Leni Natalia Zulita; Feri Hari Utami (Penerbit Jurnal Indonesia, 2021)
The objectives to be achieved in this research are: 1). Creating a Decision Support System (SPK) in receiving scholarships using the Analytical Hierarchy Process (AHP) method 2). The SPK made to determine scholarship recipients is in the form of providing assistance free of committee fees. The research method used in this research is from a conventional system to a computer system in the form of an Analytical Hierarchy Process method. The software used in making a Decision Support System (DSS) in receiving scholarships uses the Analytical Hierarchy Process method using the PHP programming language and mySQL database. The criteria in the scholarship recipient data through the Analytical Hierarchy Process method consist of report cards, academic scores and non-academic scores. The results of the Decision Support System are in the form of ranking students (students) based on the calculation of criteria and student alternatives that are calculated using the Analytical Hierarchy Process method.